Accessing the global value chain in a changing institutional environment: Comparing aeronautics and coffee - Fabrizio Cafaggi; Luana F. Joppert Swensson; Ronaldo Porto Macedo; Tiago Andreotti e Silva; Clarissa Piterman Gross; Lucila Gabriel de Almeida; Thiago Alves Ribeiro (Inter-American Development Bank (IDB), 2012)
The aim of the paper, based on empirical research in Brazil, is to investigate how supply chains have evolved over time, what factors have driven this evolution and also how a specific set of contractual practices along these chains is linked to access to international markets. The two selected case studies in the field of agriculture and aeronautics permit comparison between different modes of accessing international markets and GVCs; they illustrate the roles of transnational corporations and those of public institutions both at domestic and international levels in promoting access and determining its modes and potential spillover effects onto local production systems. More specifically, the research identifies the alternative channels of access to GVCs and international markets, and the institutional, legal and economic obstacles which prevent access or make it very costly. It looks at the role of intermediaries who control access to international markets, examining when they operate as gateways and when as bottlenecks. It examines both private and public actors, trying to disentangle when they facilitate and when they hinder access. It focuses on the most relevant factors that may attract foreign direct investments in human and physical capital to Brazil.
hdl:11319/4250
Keywords: F23; K12; L14; O54; 330; Global Value Chains; Access to International Markets; Contractual Practices; Brazil